Food security state and challenges in South Africa - Shikha Vyas-Doorgapersad (Insights into Regional Development)
The study assesses the status quo of SDG 2 implementation in South Africa. The study further examines the obstacles to achieving SDG 2 within the nation's framework. The study also looks at and assesses several national programmes related to food security. A few interventions are discussed and considered to enhance and augment the extent of food security in South Africa. The study employed a qualitative approach and used the literature review to compile information related to SDG 2 and food security interventions, which was further analyzed through document and conceptual analysis. The findings show that there are issues with the implementation of policies pertaining to food security initiatives. The study aims to answer the following questions: What obstacles need to be overcome for SDG 2 to be implemented effectively, and what measures are necessary to ensure the success of food security interventions in South Africa? Thus, the study aims to evaluate South Africa's progress toward food security (focus). It also seeks to assess the accomplishments and shortcomings of food security initiatives implemented in South Africa (locus). The sustainable livelihoods approach (SLA) is considered a theoretical framework for the study. Suggestions for improving policy are made as a contribution to the public management and governance field.